Adsorption and Incorporation of AgNPs Mediated by Seed Priming in Cultivated Taify Pomegranate: Integrated Approaches - Amal Ahmed Alyamani; Maissa M. Morsi; Hala M. Abdelmigid (Horticulturae, 2024)
A novel approach known as seed priming has been developed to improve seed germination and, ultimately, increase growth and yield. For high-value crops like pomegranates (Punica granatum) in high-altitude regions like the Taif area, affordable, sustainable, and efficient seed treatments are yet to be discovered. In this study, we employed a green synthesis method using pomegranate peel and coffee ground extracts to synthesize silver nanoparticles (AgNPs) at a concentration of 80 mg/mL. These AgNPs were then utilized to prime pomegranate seeds for 24 h. Furthermore, a chemical reduction method using trisodium citrate was used for comparison. The adsorption of NPs was verified using scanning electron microscopy (SEM) and energy dispersive X-ray (EDX), while their incorporation was confirmed by transmission electron microscopy (TEM). We further validated our EM results with X-ray fluorescence (XRF) and inductively coupled plasma–optical emission spectroscopy (ICP-OES). According to the findings of this study, AgNPs were observed to be present within seeds even after undergoing storage during priming. There is a possibility that the results obtained could potentially contribute to maintaining the quality of crops in a sustainable and eco-friendly manner.